EFFECTING THE MONITORING OF EDUCATION NATIONAL STANDARDS THROUGH THE PRINCIPLE OF WEB-BASED TRANSPARENCY IN THE OFFICE OF THE MINISTRY OF RELIGION OFFICE, PAMEKASAN DISTRICT - Mohammad Salehoddin; Moh. Badrus Syamsi (Universitas Madura, 2021)
The progress of a nation is largely determined by the quality of education. The more quality a nation's education is, the more potential it is to increase the dignity of that nation. Therefore, the government created a National Education Standard as a benchmark for minimum standards that must be achieved and even exceeded by educational units in the territory of the Republic of Indonesia. The implementation of the National Education Standards must be regularly monitored by school supervisors and reported to the relevant authorities. The principle of web-based transparency is one of the strategies that need to be taken in order to streamline the monitoring of the National Education Standards